Analytical Evaluation of RBS Moment Connection for Indian Profiles Under Seismic Behavior - Indupriya, G.; Anupriya, B. (International Journal of Sustainable Construction Engineering and Technology, 2022)
The effects of Northridge (1994) and Kobe (1995) earthquake, intensive analysis and testing efforts are currently being sought for higher ways of designing seismic resistant steel connections. A connection with RBS (Reduced beam Section) is an acceptable solution to emphasizing a moment connection and can be the most reliable type of connection. Considering the benefits of RBS connection and the lack of information on resources in Indian standards, an analytical study of RBS connections of Indian profiles is performed. This study elaborates on Indian profiles to understand the beam-column connection’s overall performance characteristics during the cyclic response. FEA study is carried out to focus on improving the plastic deformation potential of the connection. The moment capacity of the connection is strengthened by the inclusion of RBS region in the beam. The seven specimens which includes Specimen without RBS, Flange cut RBS and Flange hole RBS have been designed and evaluated using the Finite element ABAQUS program. The findings of this study revealed that specimen without RBS exhibits low Seismic activity efficiency. While RBS specimens performed well, in all instances, Flange holes specimens demonstrate good performance.